The pedagogy of silence in Auschwitz: an analysis from 174,517 (Research, Society and Development, 2019)
The objective of this article is to make an analysis of the mechanisms that made it difficult for prisoners to communicate in the Auschwitz concentration camp and the Auschwitz extermination camp guided by the witness If is this a man, from the Italian Jew Primo Levi - or 174,517, his identification number in the Field. The discussion aims to contribute to the understanding of the experience of the Lager, facing generalizations and banalizations, and to investigate the device of repression that hides between the lines of this Nazi structure. Through the idea of pedagogy of silence, it is proposed to reflect on the violence that goes beyond the physical aspects and that also contributed to the attempt of dehumanization of the prisoner. In the daily life of this borderline experience, communication appears as another element of restriction, and victims end up even appropriating silence as a strategy for their own survival; however, the testimony also allows us to observe how resistance to incommunicability occurs.